A high-performance polypropylene film, preparation method and application thereof in DC support capacitors
By adding nanozeolite imidazole skeleton material to the polypropylene film, the problem of insufficient breakdown strength and dielectric constant in new energy vehicle applications is solved, and the high dielectric constant and breakdown strength is improved, which is suitable for DC support capacitors.
Patent Information
- Application Number
- CN202311258029.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-09-27
AI Technical Summary
Domestic polypropylene films have problems with insufficient breakdown strength and dielectric constant in the application of new energy vehicles, resulting in a decrease in the stability of the capacitor and a low energy storage density.
The nanozeolite imidazole framework material (ZIF-8) was added to the polypropylene film to improve its dielectric constant and breakdown strength.
It realizes the high dielectric constant and breakdown strength of polypropylene film, and is suitable for DC-supported capacitors, improving the performance of capacitors in new energy vehicles.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of capacitor films and relates to a high-performance polypropylene film, a preparation method and application thereof in a DC support capacitor. Background Art
[0002] At present, there is still a big gap between my country's new energy vehicle capacitor film and the advanced level of foreign countries, mainly manifested in: (1) The raw materials of capacitor film are of low purity and rely on imports. The raw materials of capacitor film for new energy vehicles come from high-purity polypropylene (PP) of Borealis, which has long been monopolized by foreign countries; the gray content, isotacticity index, melt index and other properties of domestic PP for capacitor film trial-produced by Sinopec and Zhenhai Refining and Chemical are still lower than those of Borealis, and are limited to the manufacture of low-end film products. (2) The processing and molding methods and vacuum evaporation process technology of ultra-thin capacitor film are still lagging behind those of foreign countries. The yield of ultra-thin polypropylene film with excellent insulation performance suitable for flexible DC capacitors for new energy vehicles is low, and the stability of the engineering preparation process of film drawing and evaporation is poor.
[0003] The dielectric loss of domestic polypropylene film is several times or even more than ten times that of imported products, and the breakdown field strength is about 100kV / mm lower than that of imported products. As the working time of the capacitor wound with domestic polypropylene capacitor film increases, its internal temperature rises rapidly, resulting in a sharp decline in the stability of the capacitor, and even causing the capacitor to fail. The frequent heating and insulation breakdown failures of ultra-thin polypropylene film capacitors are bottleneck problems restricting the application of domestic ultra-thin capacitor films in new energy vehicles and other fields. In addition, the dielectric constant of polypropylene film is very low, which greatly limits its energy storage density. Low energy storage density means that the volume and number of capacitors need to be increased to meet application requirements, which is contrary to the development trend of electronic devices. Therefore, a polypropylene film with high anti-puncture strength and high dielectric constant is developed for use in DC support capacitors to contribute to the development of new energy vehicles.
[0004] In recent years, with the continuous development of material composite technology, researchers have found that the comprehensive performance of materials can be effectively improved through the composite of multiple components of materials, which provides the possibility of achieving the synergistic improvement of the puncture resistance and dielectric constant of polypropylene films. For example, Fan et al. (Fan Benhui, Zhou Mingyu, Zhang Chong, et al. Improved dielectric properties in polypropylene / poly (vinylidene fluoride) binary blends containing boron nitride nanosheets (BNNS): toward high voltage current application [J]. Journal of Physical Chemistry C, 2019, 123: 11993-12000) found that the blended film of polyvinylidene fluoride and polypropylene can improve the dielectric constant of polypropylene and maintain a high breakdown field strength; however, the crystallization behavior of polypropylene will be affected, and the two-phase interface produced by different polymers will increase the dielectric loss. For example, Chinese patent application CN110041619A discloses that adding nano tantalum oxide to organic plastics such as polypropylene, polyethylene, polytetrafluoroethylene or polystyrene can significantly improve the dielectric constant of organic plastics, but inevitably, the breakdown field strength of organic plastics is reduced. Chinese invention patent CN107033502B uses surface-modified neodymium-doped barium titanate nanoparticles dispersed in an organic matrix to effectively improve the dielectric constant and breakdown field strength of the composite film, but the process for obtaining surface-modified nanoparticles is very complicated and has limited effect on performance improvement. In addition, the thickness of the polypropylene film used for DC support capacitors is very small, only a few microns, and the effect of conventional nanoparticles filled in micron-level polypropylene films is very limited.
[0005] Metal-Organic Frameworks (MOFs) materials are a type of crystalline materials with three-dimensional pore structures composed of organic molecules with metal atoms as the center. The spatial combination of the metal atom center and various organic ligands makes the pore size of the material controllable and has unique physical and chemical properties. Nano-crystalline MOFs (NMOFs) not only have the properties of traditional bulk metal-organic framework materials, but also have the physical and chemical properties unique to the small size of nanomaterials. At present, there is no research on the use of MOFs materials in polypropylene films for capacitors. Summary of the invention
[0006] The purpose of the present invention is to provide a high-performance polypropylene film, a preparation method and its application in a DC support capacitor, and to obtain a polypropylene film with low thickness, high dielectric constant and high puncture strength by adding nano zeolite imidazolate skeleton material to polypropylene.
[0007] One object of the present invention is achieved by the following technical solutions:
[0008] A high-performance polypropylene film comprises a polypropylene matrix and a nano-zeolite imidazolate skeleton material (ZIF-8) dispersed in the polypropylene matrix, wherein the average particle size of the nano-zeolite imidazolate skeleton material is less than or equal to 100 nm.
[0009] Preferably, the thickness of the high-performance polypropylene film is ≤6 μm, for example, it can be 1, 2, 3, 4, 5, 6 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0010] The high-performance polypropylene film of the present invention is to be used in DC support capacitors. Its thickness is ≤6μm, which is very thin. Conventional nanoparticles are filled in polypropylene films with a thickness of ≤6μm and have very limited effects. The nano ZIF-8 selected in the present invention is composed of zinc ions Zn 2+ A type of metal-organic framework coordinated with 2-methylimidazole (2-MiM) exhibits good biocompatibility and plays a very good role in improving the performance of polypropylene films with a thickness of ≤6μm. The nano-zeolite imidazolate framework material added in the present invention has an excellent performance improvement effect on polypropylene films compared to other types of nano-metal-organic framework materials.
[0011] The preparation method of the nano zeolite imidazolate framework material selected in the present invention is not particularly limited, and can be prepared by any existing method. The following examples are provided: adding a methanol solution of zinc nitrate hexahydrate to a methanol solution of 2-methylimidazole, wherein the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:7.9-8.2, stirring the reaction for 30-45 minutes, centrifuging, washing with methanol, and then drying to obtain the nano zeolite imidazolate framework material.
[0012] Preferably, the average particle size of the nano zeolite imidazolate framework material is 10 to 80 nm, for example, any value among 10 nm, 15 nm, 20 nm, 25 nm, 40 nm, 45 nm, 50 nm, 60 nm, 70 nm, and 80 nm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0013] The average particle size of the nano-zeolite imidazolate framework material needs to be controlled. If the particle size is too small, the effect will be limited; and if the particle size is too large, the dielectric loss of polypropylene will increase and the breakdown field strength will be reduced.
[0014] Preferably, the nano-zeolite imidazolate skeleton material is 0.003-0.01wt% of the mass of the polypropylene matrix, for example, it can be any value among 0.003wt%, 0.004wt%, 0.005wt%, 0.006wt%, 0.007wt%, 0.008wt%, 0.009wt%, 0.01wt%, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0015] If the amount of nano-zeolite imidazolate skeleton material added is too low, the dielectric constant and breakdown field strength will increase only slightly, while if the amount is too high, the dielectric constant will increase, but the breakdown field strength will be greatly reduced. Only by controlling the amount of nano-zeolite imidazolate skeleton material added within a suitable range can a polypropylene film with both high dielectric constant and anti-puncture strength be obtained.
[0016] More preferably, the nano-zeolite imidazolate skeleton material accounts for 0.004-0.006 wt % of the mass of the polypropylene matrix.
[0017] Preferably, the average particle size of the nano-zeolite imidazolate framework material is 10-80 nm, and the nano-zeolite imidazolate framework material accounts for 0.004-0.006 wt % of the mass of the polypropylene matrix.
[0018] The present invention adds nano zeolite imidazolate skeleton material into polypropylene material, which is beneficial to improve the dielectric constant of polypropylene material. The nano zeolite imidazolate skeleton material has a very large specific surface area, and a large number of traps are introduced at the interface between the nano material and the polypropylene matrix, which reduces the mean free path and carrier mobility of the carriers and limits the transmission process. By controlling the addition amount and particle size of the nano zeolite imidazolate skeleton material, the nucleation center of the polypropylene film can be increased to form a denser crystal form, the PP grain boundary voids are significantly reduced, and the trap state distribution and the migration behavior of the carriers are effectively regulated.
[0019] The polypropylene matrix of the present invention is obtained by processing polypropylene raw materials. The isotactic index of the polypropylene raw materials is ≥98.0%, the melting index MFR is 3.2-4.0g / 10min (230°C, 2.16kg), and the ash content is ≤20ppm.
[0020] Preferably, the high-performance polypropylene film has a DC breakdown field strength of ≥680 kV / mm at 25° C. and a dielectric constant of ≥2.4 (1 kHz) at 25° C.
[0021] Another object of the present invention is achieved by the following technical solutions:
[0022] A method for preparing a high-performance polypropylene film comprises the following steps:
[0023] The polypropylene raw material and the nano-zeolite imidazolate skeleton material are mixed and melt-extruded to obtain a melt, and the melt is cooled and shaped to obtain a cast sheet, and the cast sheet is sequentially subjected to a longitudinal stretching step and a transverse stretching step, and then subjected to a corona treatment, winding, a first aging treatment, slitting, and a second aging treatment to obtain a polypropylene film.
[0024] Preferably, the isotactic index of the polypropylene raw material is ≥98.0%, the melt index MFR is 3.2-4.0 g / 10 min (230° C., 2.16 kg), and the ash content is ≤20 ppm.
[0025] The ash content of the polypropylene raw material is the mass ratio of the inorganic oxides remaining after the polypropylene is calcined at a high temperature of 800°C to the raw material. The ash in the polypropylene participates in the crystallization process to a certain extent, and affects the microscopic morphology of the polypropylene film; at the same time, the high ash content intensifies the ionization of impurities inside the film medium, promotes ion conduction, and increases the conduction loss. Therefore, the ash content of the polypropylene raw material selected by the present invention is controlled to be ≤20ppm. The higher the isotacticity index of the polypropylene raw material, the more uniform the arrangement of each propylene monomer in the polypropylene molecular chain, the better the crystallinity, and the dense and compact microstructure formed helps to improve the breakdown field strength of the film. The melt index MFR refers to the mass value of the thermoplastic resin at a specified temperature and load, which passes through a standard capillary within 10 minutes, expressed in grams / 10 minutes, and measured using a melt index meter. The present invention selects a polypropylene raw material with a melt index MFR of 3.2 to 4.0 g / 10min (measurement conditions: temperature of 230°C, 2160 grams of load), effectively controls the melt to better adapt to the flow rate of the extrusion system, and controls the film thickness.
[0026] Preferably, the die temperature of the melt extrusion is 230-250°C.
[0027] Preferably, the melt is cooled and shaped by passing through a chilling roller and an air shower, the temperature of the chilling roller is 95 to 110° C., and the thickness of the obtained casting sheet is 200.0 to 400.0 μm.
[0028] Preferably, the longitudinal stretching step comprises: longitudinal preheating, longitudinal stretching and longitudinal shaping, the longitudinal preheating temperature is 100-135°C, the longitudinal stretching temperature is 151-155°C and the longitudinal shaping temperature is 152-158°C.
[0029] Preferably, the longitudinal stretching ratio is 5 to 8 times.
[0030] Preferably, the transverse stretching step includes: transverse preheating, transverse stretching and transverse shaping, the transverse preheating temperature is 160-175°C, the transverse stretching temperature is 163-168°C and the transverse shaping temperature is 176-182°C.
[0031] Preferably, the transverse stretching ratio is 7 to 10 times.
[0032] In the past, the inventors set the longitudinal stretching temperature to 140-145°C, the longitudinal shaping temperature to 142-148°C, the transverse stretching temperature to 155-160°C, and the transverse shaping temperature to 165-175°C during the stretching process of the polypropylene film without adding the nano zeolite imidazolate skeleton material; while the present invention increases the longitudinal stretching temperature to 151-155°C, the longitudinal shaping temperature to 152-158°C, and the transverse stretching temperature to 163-168°C, and the transverse shaping temperature to 176-182°C. Because the polypropylene raw material of the present invention contains a small amount of nano zeolite imidazolate skeleton material, the stretching and shaping temperatures of the longitudinal stretching step and the transverse stretching step are increased to a suitable range, which is conducive to the orientation and recrystallization of the polypropylene molecular chain under the stretching action, and improves the film performance.
[0033] Preferably, the intensity of the corona treatment is 7 to 20 W·min / m 2 .
[0034] Preferably, the first aging treatment is carried out at a dust-free level of 10,000 or below, at 20 to 40° C. for 30 to 100 hours.
[0035] Preferably, the second aging treatment is carried out at a dust-free level of 10,000 or below, at 20-40° C. for 15-40 hours.
[0036] The third object of the present invention is achieved by the following technical solutions:
[0037] Application of the above high-performance polypropylene film in DC support capacitors The high-performance polypropylene film provided by the present invention has a high breakdown field strength and a slightly higher dielectric constant, and can be applied to DC support capacitors as a capacitor film.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. The present invention adds a nano-zeolite imidazolate framework material with an average particle size of ≤100nm into a polypropylene material, which has an excellent performance improvement effect on a low-thickness polypropylene film compared to other types of nano-metal-organic framework materials, and is beneficial to improving the dielectric constant of the polypropylene film and increasing the breakdown field strength;
[0040] 2. The present invention controls the addition amount of the nano-zeolite imidazolate skeleton material and the particle size within a suitable range, which can increase the nucleation center of the polypropylene film, form a denser crystal form, and obtain a polypropylene film with a high dielectric constant and puncture resistance;
[0041] 3. The present invention limits the isotactic index of the polypropylene raw material to ≥98.0%, the melt index MFR to 3.2-4.0 g / 10 min (230° C., 2.16 kg), and the ash content to ≤20 ppm; high isotactic index and low ash content are beneficial to improving the performance of the polypropylene film;
[0042] 4. The polypropylene raw material of the present invention contains a small amount of nano-zeolite imidazolate skeleton material, and the stretching and shaping temperatures of the longitudinal stretching step and the transverse stretching step are simultaneously increased to a suitable range, which is beneficial to the orientation and recrystallization of the polypropylene molecular chain under the stretching action, and improves the performance of the low-thickness polypropylene film;
[0043] 5. The high-performance polypropylene film provided by the present invention has a thickness of ≤6μm, a DC breakdown field strength of ≥680kV / mm at 25°C, and a dielectric constant of ≥2.4 (1kHz) at 25°C. It has excellent breakdown field strength and high dielectric constant, and can be used in DC support capacitors as a capacitor film to promote the development of new energy vehicles. DETAILED DESCRIPTION
[0044] The technical scheme of the present invention is further described below by specific embodiments. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended to be used for specific limitations of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0045] Polypropylene raw material was purchased from BOREALIS, model HC300BF.
[0046] Example 1
[0047] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.005 wt% of the mass of the polypropylene matrix.
[0048] ZIF-8 was prepared by the following steps: 9.87mmol Zn(NO3)2·6H2O was dissolved in 200ml methanol, 79.04mmol 2-methylimidazole was dissolved in 200ml methanol, Zn(NO3)2·6H2O was quickly poured into 2-methylimidazole, and magnetic stirring was performed. Stirring was performed for 1h, centrifuged, washed with methanol, centrifuged, and then vacuum dried at 40 degrees for 24h. The average particle size of ZIF-8 was 48nm as measured by Nicomp 380DLS dynamic light scattering.
[0049] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0050] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 3000 rpm for 5 min, wherein the mass of ZIF-8 was 0.005 wt % of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 240° C.;
[0051] 2) chilling roller and air shower cooling and shaping: the melt prepared in step 1) is cooled and shaped by chilling roller and air shower to obtain a casting sheet, and the temperature of the chilling roller is 100° C.;
[0052] 3) Longitudinal stretching step: the cast sheet obtained in step 2) is sequentially subjected to longitudinal preheating, longitudinal stretching and longitudinal shaping, wherein the longitudinal preheating has 8 rollers, the temperature of the 1st to 2nd rollers is set to 105°C, the temperature of the 3rd to 4th rollers is set to 120°C, the temperature of the 5th to 6th rollers is set to 128°C, and the temperature of the 7th to 8th rollers is set to 133°C; the longitudinal stretching has 6 rollers, the temperature of the 1st to 2nd rollers is set to 152°C, the temperature of the 3rd to 4th rollers is set to 154°C, and the temperature of the 5th to 6th rollers is set to 151°C; the longitudinal shaping has 4 rollers, the temperature of the 1st to 2nd rollers is set to 154°C, and the temperature of the 3rd to 4th rollers is set to 156°C; the longitudinal stretching ratio is 6 times;
[0053] 4) Transverse stretching step: the film obtained in step 3) is sequentially subjected to transverse preheating, transverse stretching and transverse shaping, wherein the transverse preheating has 8 sections, the temperature of sections 1 to 3 is set to 165°C, the temperature of sections 4 to 6 is set to 170°C; the temperature of sections 7 to 8 is set to 172°C; the transverse stretching has 6 sections, the temperature of sections 1 to 2 is set to 163°C, the temperature of sections 3 to 4 is set to 165°C, and the temperature of sections 5 to 6 is set to 168°C; the transverse shaping has 5 sections, the temperature of sections 1 to 3 is set to 180°C, and the temperature of sections 4 to 5 is set to 182°C; the transverse stretching ratio is 8 times;
[0054] 5) Thickness measurement, edge trimming and corona treatment: The thickness of the film was measured to be 5.0 μm. Two electrodes were used to perform corona treatment on both sides of the film at the same time. During corona treatment, the output power of the two electrodes was 6 KW, the output voltage was 6 KV, the pulse frequency was 20 KHz, the discharge gap was 2 mm, and the bombardment intensity of the electrodes was 10 W·min / m 2 The discharge state of the electrode is arc-shaped dense mist discharge, and the exhaust is a four-channel ozone extraction device;
[0055] 6) Winding: Winding tension is 20%, winding pressure is 40%;
[0056] 7) First aging treatment: The rolled film is aged in an environment with a dust-free grade of 10,000 and a temperature of 32°C for 80 hours;
[0057] 8) Slitting: Slitting the film after the first aging treatment into small rolls of film of a certain width according to the needs;
[0058] 9) Second aging treatment: The slit small roll film is aged for 20 hours in an environment with a dust-free level of 10,000 and a temperature of 30° C. to obtain a finished polypropylene film.
[0059] Example 2
[0060] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 2.5 nm, and the mass of ZIF-8 is 0.005 wt% of the mass of the polypropylene matrix.
[0061] ZIF-8 was prepared by the following steps: 1.02 g Zn(NO3)2·6H2O was dissolved in 50 mL deionized water, labeled as solution I. 1.13 g 2-methylimidazole and 1.39 g triethylamine (TEA) were dissolved in 50 mL deionized water, labeled as solution II. Then 0.9 mL of solution I and 0.9 mL of solution II were added to two 0.05 M CTAB / 0.5 M 1-hexanol / heptane mixtures (50 mL), labeled as microemulsions A and B, respectively. The two microemulsions were vigorously stirred at room temperature for 30 minutes. The two microemulsions were mixed and then stirred at 800 rpm for 1 hour at room temperature. After a series of centrifugation, filtration, and vacuum drying at 60°C for 24 hours, ZIF-8 was obtained. The average particle size of ZIF-8 measured by Nicomp 380DLS dynamic light scattering was 2.5 nm.
[0062] The preparation method of the high performance polypropylene film is the same as that of Example 1.
[0063] Example 3
[0064] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.005 wt% of the mass of the polypropylene matrix.
[0065] The preparation method of ZIF-8 is the same as that of Example 1.
[0066] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0067] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 3000 rpm for 5 min, wherein the mass of ZIF-8 was 0.006 wt% of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 240° C.;
[0068] 2) chilling roller and air shower cooling and shaping: the melt prepared in step 1) is cooled and shaped by chilling roller and air shower to obtain a casting sheet, and the temperature of the chilling roller is 100° C.;
[0069] 3) Longitudinal stretching step: the cast sheet obtained in step 2) is sequentially subjected to longitudinal preheating, longitudinal stretching and longitudinal shaping, wherein the longitudinal preheating has 8 rollers, the temperature of the 1st to 2nd rollers is set to 105°C, the temperature of the 3rd to 4th rollers is set to 120°C, the temperature of the 5th to 6th rollers is set to 128°C, and the temperature of the 7th to 8th rollers is set to 133°C; the longitudinal stretching has 6 rollers, the temperature of the 1st to 2nd rollers is set to 141°C, the temperature of the 3rd to 4th rollers is set to 144°C, and the temperature of the 5th to 6th rollers is set to 142°C; the longitudinal shaping has 4 rollers, the temperature of the 1st to 2nd rollers is set to 145°C, and the temperature of the 3rd to 4th rollers is set to 147°C; the longitudinal stretching ratio is 6 times;
[0070] 4) Transverse stretching step: the film obtained in step 3) is sequentially subjected to transverse preheating, transverse stretching and transverse shaping, wherein the transverse preheating has 8 sections, the temperature of sections 1 to 3 is set to 165°C, the temperature of sections 4 to 6 is set to 170°C; the temperature of sections 7 to 8 is set to 172°C; the transverse stretching has 6 sections, the temperature of sections 1 to 2 is set to 156°C, the temperature of sections 3 to 4 is set to 158°C, and the temperature of sections 5 to 6 is set to 160°C; the transverse shaping has 5 sections, the temperature of sections 1 to 3 is set to 170°C, and the temperature of sections 4 to 5 is set to 173°C; the transverse stretching ratio is 8 times;
[0071] Step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0072] Example 4
[0073] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.001 wt% of the mass of the polypropylene matrix.
[0074] The preparation method of ZIF-8 is the same as that of Example 1.
[0075] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0076] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 3000 rpm for 5 min, wherein the mass of ZIF-8 was 0.001 wt% of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 240° C.;
[0077] Step 2), step 3), step 4), step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0078] Example 5
[0079] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.003 wt% of the mass of the polypropylene matrix.
[0080] The preparation method of ZIF-8 is the same as that of Example 1.
[0081] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0082] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 3000 rpm for 5 min, wherein the mass of ZIF-8 was 0.003 wt % of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 240° C.;
[0083] Step 2), step 3), step 4), step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0084] Example 6
[0085] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.004 wt% of the mass of the polypropylene matrix.
[0086] The preparation method of ZIF-8 is the same as that of Example 1.
[0087] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0088] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 3000 rpm for 5 min, wherein the mass of ZIF-8 was 0.004 wt% of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 240° C.;
[0089] Step 2), step 3), step 4), step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0090] Example 7
[0091] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.006 wt% of the mass of the polypropylene matrix.
[0092] The preparation method of ZIF-8 is the same as that of Example 1.
[0093] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0094] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 3000 rpm for 5 min, wherein the mass of ZIF-8 was 0.006 wt% of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 240° C.;
[0095] Step 2), step 3), step 4), step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0096] Example 8
[0097] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.008 wt% of the mass of the polypropylene matrix.
[0098] The preparation method of ZIF-8 is the same as that of Example 1.
[0099] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0100] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 3000 rpm for 5 min, wherein the mass of ZIF-8 was 0.008 wt% of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 240° C.;
[0101] Step 2), step 3), step 4), step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0102] Example 9
[0103] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.01 wt% of the mass of the polypropylene matrix.
[0104] The preparation method of ZIF-8 is the same as that of Example 1.
[0105] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0106] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 3000 rpm for 5 min, wherein the mass of ZIF-8 was 0.01 wt% of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 240° C.;
[0107] Step 2), step 3), step 4), step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0108] Example 10
[0109] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.015 wt% of the mass of the polypropylene matrix.
[0110] The preparation method of ZIF-8 is the same as that of Example 1.
[0111] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0112] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 3000 rpm for 5 min, the mass of ZIF-8 being 0.015 wt % of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 240° C.;
[0113] Step 2), step 3), step 4), step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0114] Embodiment 11
[0115] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.03 wt% of the mass of the polypropylene matrix.
[0116] The preparation method of ZIF-8 is the same as that of Example 1.
[0117] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0118] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 3000 rpm for 5 min, wherein the mass of ZIF-8 was 0.03 wt % of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 240° C.;
[0119] Step 2), step 3), step 4), step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0120] Example 12
[0121] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.004 wt% of the mass of the polypropylene matrix.
[0122] ZIF-8 was prepared by the following steps: 9.87mmol Zn(NO3)2·6H2O was dissolved in 200ml methanol, 79.04mmol 2-methylimidazole was dissolved in 200ml methanol, Zn(NO3)2·6H2O was quickly poured into 2-methylimidazole, and magnetic stirring was performed. Stirring was performed for 1h, centrifuged, washed with methanol, centrifuged, and then vacuum dried at 40 degrees for 24h. The average particle size of ZIF-8 was 48nm as measured by Nicomp 380DLS dynamic light scattering.
[0123] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0124] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 5000 rpm for 6 min, wherein the mass of ZIF-8 was 0.004 wt% of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 235° C.;
[0125] 2) chilling roller and air shower cooling and shaping: the melt prepared in step 1) is cooled and shaped by chilling roller and air shower to obtain a casting sheet, and the temperature of the chilling roller is 95° C.;
[0126] 3) Longitudinal stretching step: the cast sheet obtained in step 2) is sequentially subjected to longitudinal preheating, longitudinal stretching and longitudinal shaping, wherein the longitudinal preheating has 8 rollers, the temperature of the 1st to 2nd rollers is set to 103°C, the temperature of the 3rd to 4th rollers is set to 122°C, the temperature of the 5th to 6th rollers is set to 127°C, and the temperature of the 7th to 8th rollers is set to 132°C; the longitudinal stretching has 6 rollers, the temperature of the 1st to 2nd rollers is set to 152°C, the temperature of the 3rd to 4th rollers is set to 153°C, and the temperature of the 5th to 6th rollers is set to 151°C; the longitudinal shaping has 4 rollers, the temperature of the 1st to 2nd rollers is set to 154°C, and the temperature of the 3rd to 4th rollers is set to 155°C; the longitudinal stretching ratio is 7 times;
[0127] 4) Transverse stretching step: the film obtained in step 3) is sequentially subjected to transverse preheating, transverse stretching and transverse shaping, wherein the transverse preheating has 8 sections, the temperature of sections 1 to 3 is set to 164°C, the temperature of sections 4 to 6 is set to 169°C; the temperature of sections 7 to 8 is set to 170°C; the transverse stretching has 6 sections, the temperature of sections 1 to 2 is set to 164°C, the temperature of sections 3 to 4 is set to 166°C, and the temperature of sections 5 to 6 is set to 168°C; the transverse shaping has 5 sections, the temperature of sections 1 to 3 is set to 178°C, and the temperature of sections 4 to 5 is set to 180°C; the transverse stretching ratio is 9 times;
[0128] 5) Thickness measurement, trimming and corona treatment: The thickness of the film was measured to be 4.5 μm. Two electrodes were used to perform corona treatment on both sides of the film at the same time. During corona treatment, the output power of the two electrodes was 8 KW, the output voltage was 7 KV, the pulse frequency was 20 KHz, the discharge gap was 2 mm, and the bombardment intensity of the electrodes was 12 W·min / m 2 The discharge state of the electrode is arc-shaped dense mist discharge, and the exhaust is a four-channel ozone extraction device;
[0129] 6) Winding: Winding tension is 20%, winding pressure is 40%;
[0130] 7) First aging treatment: The rolled film is aged in an environment with a dust-free grade of 10,000 and a temperature of 30°C for 90 hours;
[0131] 8) Slitting: Slitting the film after the first aging treatment into small rolls of film of a certain width according to the needs;
[0132] 9) Second aging treatment: The slit small roll film is aged for 18 hours in an environment with a dust-free level of 10,000 and a temperature of 30° C. to obtain a finished polypropylene film.
[0133] Embodiment 13
[0134] The high-performance polypropylene film of this embodiment is formed by a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 48 nm, and the mass of ZIF-8 is 0.005 wt% of the mass of the polypropylene matrix.
[0135] ZIF-8 was prepared by the following steps: 9.87mmol Zn(NO3)2·6H2O was dissolved in 200ml methanol, 79.04mmol 2-methylimidazole was dissolved in 200ml methanol, Zn(NO3)2·6H2O was quickly poured into 2-methylimidazole, and magnetic stirring was performed. Stirring was performed for 1h, centrifuged, washed with methanol, centrifuged, and then vacuum dried at 40 degrees for 24h. The average particle size of ZIF-8 was 48nm as measured by Nicomp 380DLS dynamic light scattering.
[0136] The high performance polypropylene film of this embodiment is prepared by the following steps:
[0137] 1) A polypropylene raw material and ZIF-8 with an average particle size of 48 nm were stirred and mixed at 2000 rpm for 10 min, wherein the mass of ZIF-8 was 0.005 wt % of the mass of the polypropylene raw material, and the mixture was put into an extruder to extrude a melt, and the die temperature of the extruder was 245° C.;
[0138] 2) chilling roller and air shower cooling and shaping: the melt prepared in step 1) is cooled and shaped by chilling roller and air shower to obtain a casting sheet, and the temperature of the chilling roller is 105°C;
[0139] 3) Longitudinal stretching step: the cast sheet obtained in step 2) is sequentially subjected to longitudinal preheating, longitudinal stretching and longitudinal shaping, wherein the longitudinal preheating has 8 rollers, the temperature of the 1st to 2nd rollers is set to 106°C, the temperature of the 3rd to 4th rollers is set to 123°C, the temperature of the 5th to 6th rollers is set to 129°C, and the temperature of the 7th to 8th rollers is set to 134°C; the longitudinal stretching has 6 rollers, the temperature of the 1st to 2nd rollers is set to 153°C, the temperature of the 3rd to 4th rollers is set to 155°C, and the temperature of the 5th to 6th rollers is set to 152°C; the longitudinal shaping has 4 rollers, the temperature of the 1st to 2nd rollers is set to 155°C, and the temperature of the 3rd to 4th rollers is set to 157°C; the longitudinal stretching ratio is 5 times;
[0140] 4) Transverse stretching step: the film obtained in step 3) is sequentially subjected to transverse preheating, transverse stretching and transverse shaping, wherein the transverse preheating has 8 sections, the temperature of sections 1 to 3 is set to 166°C, the temperature of sections 4 to 6 is set to 172°C; the temperature of sections 7 to 8 is set to 174°C; the transverse stretching has 6 sections, the temperature of sections 1 to 2 is set to 163°C, the temperature of sections 3 to 4 is set to 165°C, and the temperature of sections 5 to 6 is set to 167°C; the transverse shaping has 5 sections, the temperature of sections 1 to 3 is set to 181°C, and the temperature of sections 4 to 5 is set to 182°C; the transverse stretching ratio is 8 times;
[0141] 5) Thickness measurement, trimming and corona treatment: The thickness of the film was measured to be 5.5 μm. Two electrodes were used to perform corona treatment on both sides of the film at the same time. During corona treatment, the output power of the two electrodes was 5 KW, the output voltage was 5 KV, the pulse frequency was 20 KHz, the discharge gap was 2 mm, and the bombardment intensity of the electrodes was 8 W·min / m 2 The discharge state of the electrode is arc-shaped dense mist discharge, and the exhaust is a four-channel ozone extraction device;
[0142] 6) Winding: Winding tension is 20%, winding pressure is 40%;
[0143] 7) First aging treatment: The rolled film is aged in an environment with a dust-free grade of 10,000 and a temperature of 35°C for 72 hours;
[0144] 8) Slitting: Slitting the film after the first aging treatment into small rolls of film of a certain width according to the needs;
[0145] 9) Second aging treatment: The slit small roll film is aged for 22 hours in an environment with a dust-free level of 10,000 and a temperature of 32° C. to obtain a finished polypropylene film.
[0146] Comparative Example 1
[0147] The polypropylene film of Comparative Example 1 was prepared by the following steps:
[0148] 1) Putting the polypropylene raw material into an extruder to extrude a melt, the die head temperature of the extruder is 240° C.;
[0149] 2) chilling roller and air shower cooling and shaping: the melt prepared in step 1) is cooled and shaped by chilling roller and air shower to obtain a casting sheet, and the temperature of the chilling roller is 100° C.;
[0150] 3) Longitudinal stretching step: the cast sheet obtained in step 2) is sequentially subjected to longitudinal preheating, longitudinal stretching and longitudinal shaping, wherein the longitudinal preheating has 8 rollers, the temperature of the 1st to 2nd rollers is set to 105°C, the temperature of the 3rd to 4th rollers is set to 120°C, the temperature of the 5th to 6th rollers is set to 128°C, and the temperature of the 7th to 8th rollers is set to 133°C; the longitudinal stretching has 6 rollers, the temperature of the 1st to 2nd rollers is set to 141°C, the temperature of the 3rd to 4th rollers is set to 144°C, and the temperature of the 5th to 6th rollers is set to 142°C; the longitudinal shaping has 4 rollers, the temperature of the 1st to 2nd rollers is set to 145°C, and the temperature of the 3rd to 4th rollers is set to 147°C; the longitudinal stretching ratio is 6 times;
[0151] 4) Transverse stretching step: the film obtained in step 3) is sequentially subjected to transverse preheating, transverse stretching and transverse shaping, wherein the transverse preheating has 8 sections, the temperature of sections 1 to 3 is set to 165°C, the temperature of sections 4 to 6 is set to 170°C; the temperature of sections 7 to 8 is set to 172°C; the transverse stretching has 6 sections, the temperature of sections 1 to 2 is set to 156°C, the temperature of sections 3 to 4 is set to 158°C, and the temperature of sections 5 to 6 is set to 160°C; the transverse shaping has 5 sections, the temperature of sections 1 to 3 is set to 170°C, and the temperature of sections 4 to 5 is set to 173°C; the transverse stretching ratio is 8 times;
[0152] Step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0153] Comparative Example 2
[0154] The polypropylene film of Comparative Example 2 was prepared by the following steps:
[0155] 1) Putting the polypropylene raw material into an extruder to extrude a melt, the die head temperature of the extruder is 240° C.;
[0156] 2) chilling roller and air shower cooling and shaping: the melt prepared in step 1) is cooled and shaped by chilling roller and air shower to obtain a casting sheet, and the temperature of the chilling roller is 100° C.;
[0157] 3) Longitudinal stretching step: the cast sheet obtained in step 2) is sequentially subjected to longitudinal preheating, longitudinal stretching and longitudinal shaping, wherein the longitudinal preheating has 8 rollers, the temperature of the 1st to 2nd rollers is set to 105°C, the temperature of the 3rd to 4th rollers is set to 120°C, the temperature of the 5th to 6th rollers is set to 128°C, and the temperature of the 7th to 8th rollers is set to 133°C; the longitudinal stretching has 6 rollers, the temperature of the 1st to 2nd rollers is set to 152°C, the temperature of the 3rd to 4th rollers is set to 154°C, and the temperature of the 5th to 6th rollers is set to 151°C; the longitudinal shaping has 4 rollers, the temperature of the 1st to 2nd rollers is set to 154°C, and the temperature of the 3rd to 4th rollers is set to 156°C; the longitudinal stretching ratio is 6 times;
[0158] 4) Transverse stretching step: the film obtained in step 3) is sequentially subjected to transverse preheating, transverse stretching and transverse shaping, wherein the transverse preheating has 8 sections, the temperature of sections 1 to 3 is set to 165°C, the temperature of sections 4 to 6 is set to 170°C; the temperature of sections 7 to 8 is set to 172°C; the transverse stretching has 6 sections, the temperature of sections 1 to 2 is set to 163°C, the temperature of sections 3 to 4 is set to 165°C, and the temperature of sections 5 to 6 is set to 168°C; the transverse shaping has 5 sections, the temperature of sections 1 to 3 is set to 180°C, and the temperature of sections 4 to 5 is set to 182°C; the transverse stretching ratio is 8 times;
[0159] Step 5), step 6), step 7), step 8) and step 9) are the same as those in Example 1.
[0160] Comparative Example 3
[0161] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses MIL-101 (Cr) as an additive. Specifically:
[0162] The polypropylene film of Comparative Example 3 is formed of a polypropylene matrix and MIL-101(Cr) dispersed in the polypropylene matrix, the average particle size of MIL-101(Cr) is 62 nm, and the mass of MIL-101(Cr) is 0.001 wt % of the mass of the polypropylene matrix.
[0163] MIL-101(Cr) was prepared by the following steps: 400g of chromium nitrate nine hydrate, 166g of terephthalic acid and 5L of deionized water were added to a hydrothermal reactor, stirred at 25°C for 10min, then 2158g of acetic acid was added for reaction, the reactor was heated to 200°C at a rate of 1°C / min, and the temperature was kept at this temperature for 8h; finally, the cooling rate was controlled, and the reactor was cooled to room temperature at a rate of 0.5°C / min, and the MIL-101(Cr) material was finally obtained after washing, filtering and drying. The average particle size of the MIL-101(Cr) material measured by Nicomp380DLS dynamic light scattering was 62nm.
[0164] The preparation method of the polypropylene film is the same as that of Example 1.
[0165] Comparative Example 4
[0166] The difference between Comparative Example 4 and Comparative Example 3 is that in Comparative Example 4, the mass of MIL-101 (Cr) is 0.005 wt % of the mass of the polypropylene matrix, and the rest is the same as Comparative Example 3.
[0167] Comparative Example 5
[0168] The difference between Comparative Example 5 and Comparative Example 3 is that in Comparative Example 5, the mass of MIL-101 (Cr) is 0.01 wt % of the mass of the polypropylene matrix, and the rest is the same as Comparative Example 3.
[0169] Comparative Example 6
[0170] The polypropylene film of Comparative Example 6 is formed of a polypropylene matrix and ZIF-8 dispersed in the polypropylene matrix, the average particle size of ZIF-8 is 310 nm, and the mass of ZIF-8 is 0.005 wt% of the mass of the polypropylene matrix.
[0171] ZIF-8 is XFF14 sold by Xianfeng Nano. The average particle size of ZIF-8 measured by Nicomp 380DLS dynamic light scattering is 310 nm.
[0172] The preparation method of the high performance polypropylene film is the same as that of Example 1.
[0173] Experimental Results
[0174] The dielectric constant, dielectric loss and breakdown field strength of the polypropylene films of Examples 1-13 and Comparative Examples 1-6 were tested, and the results are shown in Table 1 below.
[0175] The relative dielectric constant (εr) and dielectric loss (tanδ) of the films were measured at 25 °C using a broadband dielectric spectrometer (NG-80, Novocontrol Gmb H, Germany) in the range of 10-10 6Hz. Before testing the film, apply conductive silver paste on the film surface and dry it at 40℃ before testing.
[0176] The following is the specific test method for breakdown field strength:
[0177] 1. Test equipment
[0178] Adopt CDI-20 withstand voltage strength tester, DC electrical strength (50-point electrode method).
[0179] 2. Sample
[0180] Take three rectangular specimens of no less than 450mm×650mm. The specimens must be kept clean, flat, without wrinkles or damage.
[0181] 3. Electrode
[0182] The upper electrode is a brass cylindrical electrode with a diameter of 25 mm, a chamfer radius of 2.5 mm, and a height of 120 mm, and the working surface roughness Ra is less than 1.25 μm.
[0183] A piece of rubber about 3 mm thick with a Shore A hardness of (60-70) HA is placed on the platform, and an annealed aluminum foil is placed on the rubber as the lower electrode.
[0184] Ensure that the working surface of the electrode is flat, smooth and free of scratches.
[0185] 4. Breakdown device
[0186] The capacity of the high-voltage test transformer should ensure that the secondary rated current is not less than 0.1A. The voltage ripple coefficient of the DC power supply should not exceed 5%, and the protection resistance is (0.2~0.5)Ω / V. The voltage regulator should be able to adjust the voltage evenly. The overcurrent relay should have sufficient sensitivity to ensure that the power supply is cut off within 0.1s when the sample breaks down. The operating current should be selected with an appropriate value to avoid failure to operate after breakdown or malfunction due to failure to break down. The voltage measurement error should not exceed 4%.
[0187] 5. Test steps
[0188] a) Place the sample on the lower electrode at 25°C and use the continuous voltage increase method.
[0189] b) Set the boost speed to 500V / s.
[0190] c) Measure 50 points evenly spaced on the specimen.
[0191] d) Thickness test: Use a thickness gauge to test 40 points evenly at equal intervals on the test sample, and take the arithmetic mean as the thickness of the sample.
[0192] 6. Results
[0193] Remove the maximum and minimum values from the 50 points of breakdown measurement, and calculate the arithmetic mean of the remaining 40 points. Divide the average breakdown voltage by the sample thickness to get the average electrical strength of the batch of films.
[0194] Table 1 Performance data of polypropylene films of Examples 1-13 and Comparative Examples 1-6
[0195] Dielectric constant (1kHz) Dielectric loss (1kHz) Breakdown field strength (25℃, kV / mm) Example 1 2.72 0.0001 880 Example 2 2.67 0.0001 830 Example 3 2.64 0.0002 795 Example 4 2.45 0.0001 720 Example 5 2.60 0.0001 839 Example 6 2.69 0.0001 871 Example 7 2.73 0.0002 863 Example 8 2.74 0.0003 822 Example 9 2.75 0.0004 738 Example 10 2.75 0.0010 620 Embodiment 11 2.79 0.0018 540 Example 12 2.68 0.0001 865 Example 13 2.70 0.0002 870 Comparative Example 1 2.22 0.0001 645 Comparative Example 2 2.20 0.0001 601 Comparative Example 3 2.33 0.0003 620 Comparative Example 4 2.42 0.0014 578 Comparative Example 5 2.48 0.0024 515 Comparative Example 6 2.59 0.0005 578
[0196] Comparative Example 1 is a conventional polypropylene film without adding nano ZIF-8, and adopts conventional stretching and shaping temperature to obtain. By comparing Comparative Example 1 and Example 3, it can be known that adding a small amount of nano ZIF-8 in polypropylene film helps to improve the dielectric constant and the breakdown field strength of polypropylene film, and when further improving the stretching temperature and shaping temperature in the stretching process, the performance of polypropylene film is better (see Example 1). Comparative Example 2 does not add nano ZIF-8, but adopts the polypropylene film obtained by stretching and shaping temperature of the present invention. By comparing the experimental results of Comparative Example 1 and Comparative Example 2, it can be known that when nano ZIF-8 is not added, adopting slightly higher temperature to stretch and shape has an adverse effect on film performance. Only when nano ZIF-8 is added in polypropylene, stretching and shaping temperature are improved again, more excellent effect can be obtained.
[0197] By comparing Examples 1-2 and Comparative Example 6, it can be seen that when the average particle size of the added nano ZIF-8 is 49 nm, the improvement in the polypropylene film effect is better than that of adding nano ZIF-8 with an average particle size of 2.5 nm, while when adding nano ZIF-8 with an average particle size greater than 100 nm, the breakdown field strength is reduced.
[0198] By comparing Example 1 and Examples 4-11, it can be seen that controlling the addition amount of nano ZIF-8 has a great influence on the breakdown field strength.
[0199] Comparative Examples 3-5 show that when MIL-101(Cr) is added to polypropylene to prepare a film, the breakdown field strength of the film is greatly reduced.
[0200] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0201] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0202] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A high performance polypropylene film, characterized in that: The high-performance polypropylene film comprises a polypropylene matrix and a nano-zeolite imidazolate skeleton material dispersed in the polypropylene matrix, wherein the average particle size of the nano-zeolite imidazolate skeleton material is ≤100 nm; The nano-zeolite imidazolate skeleton material is 0.003-0.01wt% of the mass of the polypropylene matrix; The nano zeolite imidazolate framework material is nano ZIF-8.
2. A high performance polypropylene film according to claim 1, characterized in that: The thickness of the high-performance polypropylene film is ≤6 μm.
3. A high performance polypropylene film according to claim 1, characterized in that: The average particle size of the nano-zeolite imidazolate framework material is 10-80 nm.
4. A high performance polypropylene film according to claim 1, characterized in that: The nano-zeolite imidazolate skeleton material is 0.004-0.006wt% of the mass of the polypropylene matrix.
5. A high performance polypropylene film according to claim 1, characterized in that: The high-performance polypropylene film has a DC breakdown field strength of ≥680 kV / mm at 25° C. and a dielectric constant of ≥2.4 at 25° C. and 1 kHz.
6. The method for preparing a high-performance polypropylene film according to claim 1, characterized in that: The following steps are involved: The polypropylene raw material and the nano-zeolite imidazolate skeleton material are mixed and melt-extruded to obtain a melt, and the melt is cooled and shaped to obtain a cast sheet, and the cast sheet is sequentially subjected to a longitudinal stretching step and a transverse stretching step, and then subjected to a corona treatment, winding, a first aging treatment, slitting, and a second aging treatment to obtain a polypropylene film.
7. The preparation method according to claim 6, characterized in that: The isotactic index of the polypropylene raw material is ≥98.0%, the melting index MFR at 230° C. and 2.16 kg is 3.2-4.0 g / 10 min, and the ash content is ≤20 ppm.
8. The preparation method according to claim 6, characterized in that: The melt is cooled and shaped by passing through chilled rollers and air showers. The temperature of the chilled rollers is 95-110°C, and the thickness of the obtained casting sheet is 200.0-400.0 μm.
9. The preparation method according to claim 6, characterized in that: The longitudinal stretching step includes: longitudinal preheating, longitudinal stretching and longitudinal shaping, the longitudinal preheating temperature is 100-135°C, the longitudinal stretching temperature is 151-155°C and the longitudinal shaping temperature is 152-158°C.
10. The preparation method according to claim 6 or 9, characterized in that: The longitudinal stretching ratio is 5 to 8 times.
11. The preparation method according to claim 6, characterized in that: The transverse stretching step includes: transverse preheating, transverse stretching and transverse shaping, the transverse preheating temperature is 160-175°C, the transverse stretching temperature is 163-168°C and the transverse shaping temperature is 176-182°C.
12. The preparation method according to claim 6 or 11, characterized in that: The transverse stretching ratio is 7 to 10 times.
13. The preparation method according to claim 6, characterized in that: The first aging treatment is carried out at a dust-free level of 10,000 or below, at 20-40°C for 30-100 hours.
14. The preparation method according to claim 6, characterized in that: The second aging treatment is carried out at a dust-free level of 10,000 or below, at 20-40°C for 15-40 hours.
15. Use of the high-performance polypropylene film as claimed in claim 1 in a DC support capacitor.
Citation Information
Patent Citations
A simple high-energy-density neodymium-doped barium titanate / organic substrate composite film and its preparation method
CN107033502B
Plastic film with high dielectric constant and manufacturing method thereof
CN110041619A
Zeolite imidazate framework material reinforcement flame-retardant polylactic acid membrane and preparation method thereof
CN105885372A
Production process of high-energy-storage polypropylene capacitor film
CN116120608A